CCNP Security Virtual Private Networks SVPN 300-730 Official Cert Guide - Muniz, Joseph; Chimes, Steven; Risler, James (Cisco Press, 2021)
This is Cisco's official, comprehensive self-study resource for Ciscos SVPN 300-730 exam (Implementing Secure Solutions with Virtual Private Networks), one of the most popular concentration exams required for the Cisco Certified Network Professional (CCNP) Security certification. It will thoroughly prepare network professionals to deliver secure solutions based on Cisco VPN technologies. Designed for all CCNP Security candidates, CCNP Security Virtual Private Networks SVPN 300-730 Official Cert Guide covers every SVPN #300-730 objective concisely and logically, with extensive teaching features designed to promote retention and understanding. You'll find: Pre-chapter quizzes to assess knowledge upfront and focus your study more efficiently Foundation topics sections that explain concepts and configurations, and link theory to practice Key topics sections calling attention to every figure, table, and list you must know Exam Preparation sections with additional chapter review features Final preparation chapter providing tools and a complete final study plan A customizable practice test library CCNP Security Virtual Private Networks SVPN 300-730 Official Cert Guide offers comprehensive, up-to-date coverage of all SVPN #300-730 topics related to: Secure communications Architectures Troubleshooting.